Resposta do milho pipoca às doses e épocas de aplicação do nitrogênio em adubação de cobertura - Pricinotto, Luiz Fernando (2009)
The objective of this work was to evaluate the responses of the popcorn in the productivity, in the characteristics of the plant and in the quality of the popcorn, in function of the manure with nitrogen (N) in covering. The work was conducted in Fazenda Experimental de Iguatemi, of the Universidade Estadual de Maringá, during the summer harvest of 2007/2008 and the autumn/fall of 2008. The experiments was installed in a blocks with treatments completely randomized, in the factorial design of 5 x 2 x 2 + 2, in that they were studied five N shots in covering, applied in two fenologic stadiums of two cultivate of popcorn (a variety and a hybrid), with two additional treatments (shot of 180kg ha-1 fractional, for each to cultivate) with four repetitions. The data were submitted to analyses of variance and regression. The popcorn characteristics evaluated were: plant height, height of the ear insert, index of foliar area, length of the ear, number of the grains for row, mass of the grains for ear, mass of the a thousand grains, productivity and expansion capacity. In the "summer", the characteristics of the aerial part of the plants of the popcorn were not influenced by nitrogen fertilization, while the components of production to respond positively to N applied in coverage, especially in the BRS-Angela, even with the occurrence of water deficit. In the period of the "autumn", the nitrogen provided positive responses on the characteristics of the aerial part of the plants. The components of production were affected by low temperatures, in both cultivars, in the "autumn", even so, the grain yield of the cultivar IAC-125 responded positively to nitrogen fertilization. The use of manure with nitrogen in covering didn't interfere in the expansion capacity of the it cultivate of popcorn in both appraised periods.